2012
DOI: 10.1016/j.bbrc.2012.03.097
|View full text |Cite
|
Sign up to set email alerts
|

Identification of distinct physiochemical properties of toxic prefibrillar species formed by Aβ peptide variants

Abstract: The formation of amyloid-β peptide (Aβ) aggregates at an early stage during the selfassembly process is an important factor in the development of Alzheimer's disease. The toxic effect is believed to be exerted by prefibrillar species of Aβ. It is therefore important to identify which prefibrillar species are toxic and characterize their distinct properties. In the present study, we investigated the in vitro aggregation behavior of Aβ-derived peptides possessing different levels of neurotoxic activity, using fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…Several of these mutations occur in the Aβ peptide, the cleavage product produced by the processing of AβPP with β-secretase followed by γ-secretase, and a clear positive correlation has been found between the ability of the peptide to form prefibrillar aggregates and cytotoxicity (Brorsson et al, 2010; Göransson et al, 2012; Luheshi et al, 2007). The longer and more hydrophobic Aβ 1-42 peptide is more likely to form prefibrillar aggregates compared to the shorter and less hydrophobic Aβ 1-40 peptide (Dahlgren et al, 2002), and in the sporadic form of AD, it is known that an increased ratio of Aβ 1-42 to Aβ 1-40 correlates with an increased risk of subsequently developing AD (Kumar-Singh et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several of these mutations occur in the Aβ peptide, the cleavage product produced by the processing of AβPP with β-secretase followed by γ-secretase, and a clear positive correlation has been found between the ability of the peptide to form prefibrillar aggregates and cytotoxicity (Brorsson et al, 2010; Göransson et al, 2012; Luheshi et al, 2007). The longer and more hydrophobic Aβ 1-42 peptide is more likely to form prefibrillar aggregates compared to the shorter and less hydrophobic Aβ 1-40 peptide (Dahlgren et al, 2002), and in the sporadic form of AD, it is known that an increased ratio of Aβ 1-42 to Aβ 1-40 correlates with an increased risk of subsequently developing AD (Kumar-Singh et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In this situation, even a small amount (picomolar concentrations) of accumulated Aβ peptides might be enough to cause fatal damage to the cell (Zheng et al, 2009; Zheng et al, 2011). On the other hand, it is known that aggregated forms of the Aβ 1-42 peptide possess cytotoxic properties when exposed to cells at nano- to micromolar concentrations in vitro , revealing a direct toxic action of the Aβ 1-42 peptide on the cell surface (Göransson et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies of recombinant proteins have also shown that LCOs with a repeating backbone of at least five thiophene units identify non-thioflavinophilic pre-fibrillar species that precede the formation of mature amyloid fibrils. [8,12,41,42] Whether the p-FTAA staining of inclusion bodies negative for Congo Red and ThS reflects its higher sensitivity or fundamental differences in the biophysical properties of the detected protein inclusion bodies is not known; however, the p-FTAA staining was restricted to s-IBM cases (Table S1) and to inclusion bodies that were stained by antibodies to proteins reported to be present in s-IBM inclusion bodies, thereby proving its high specificity. [18][19][20][21][22][23][24] The Congo Red-and ThS-staining results also revealed that the color of p-FTAA did not determine whether the inclusion bodies were labeled with these classical amyloid ligands or not.…”
Section: Full Papersmentioning
confidence: 99%
“…Sometimes, for not fully known reasons, proteins get cleaved on the wrong amino-acid sequence by the cleaving enzymes and accumulate in the form of misfolding proteins that causes diseases or dysfunctions in the body. AD has been associated with two groups of such misfolding proteins called amyloid beta (Aβ or Abeta) and tau protein (Göransson 2012;Göransson et al 2012;Whitehouse et al 2000). When a body is younger, it circulates the amyloid peptide deposit, whereas as the body ages, it pollutes itself in overproduction of A-beta peptides while at the same time losing the ability to circulate the deposits as efficiently as in its younger years (Sadowski and Wisniewski 2004).…”
Section: Resultsmentioning
confidence: 99%
“…all of my informants jumped into discussion of the basic sciences and molecular biology: genes, proteins, enzymes, neurons and molecular agents. In these labs, AD was thought about, made and understood as the fundamental molecular processes of the body-as proteins aggregating, organizing themselves, folding and misfolding (see, e.g., Göransson et al 2012;Helmfors et al 2015).…”
Section: Resultsmentioning
confidence: 99%